2014
DOI: 10.3109/02770903.2014.912302
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, asthma and exhaled nitric oxide in U.S. Adults, 2007–2010

Abstract: Our results suggest that in the U.S. adult population, BMI is not associated with eosinophilic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
(34 reference statements)
0
2
2
Order By: Relevance
“…Studies that examined associations between adiposity and FENO are scarce and showed that higher BMI, percent body fat, and waist circumference were associated with an increased risk of current asthma in individuals with a low to normal FENO, 26 or showed no associations between BMI and FENO. 27,28 Differences in results with our study might be explained by the limitations of BMI, which does not distinguish fat mass from free-fat mass, the use of different obesity measures such as waist circumference, and age at time of measurement.…”
Section: Comparison With Previous Studiescontrasting
confidence: 73%
“…Studies that examined associations between adiposity and FENO are scarce and showed that higher BMI, percent body fat, and waist circumference were associated with an increased risk of current asthma in individuals with a low to normal FENO, 26 or showed no associations between BMI and FENO. 27,28 Differences in results with our study might be explained by the limitations of BMI, which does not distinguish fat mass from free-fat mass, the use of different obesity measures such as waist circumference, and age at time of measurement.…”
Section: Comparison With Previous Studiescontrasting
confidence: 73%
“…These findings, therefore, suggest a less favorable effect on airway inflammation of ICS in obese patients with asthma. In contrast to the study by Telenga et al [7], an association between obesity and eosinophilic airway inflammation has not been reported from previous studies [8][9][10].…”
contrasting
confidence: 53%
“…The increase in FENO observed in Cohort 2 may also relate (in part) to the increase in BMI seen during ivacaftor treatment. Weak positive associations between FENO and BMI have been observed in large cross-sectional studies, but these observations have been inconsistent across studies (independent of CF diagnosis) [36][37][38]. Finally, although we did measure adherence to therapies outside of the hospitalized setting, the actual use of concomitant medications during outpatient visits is unknown.…”
Section: Discussionmentioning
confidence: 83%